Project x: when animals invade - Rhodes, Chloe; Stuart, J. (Oxford University Press Karachi, 2009)
A thrilling adventure that follows a group of friends who find themselves in a chaotic situation when animals mysteriously begin to invade their town. As strange occurrences escalate, the friends uncover a secret experiment gone wrong, leading to wildlife becoming dangerously aggressive. They must work together to uncover the truth, devise a plan to protect their community, and restore balance before it's too late. Themes of friendship, courage, and environmental responsibility weave throughout the narrative, emphasizing the impact of human actions on nature.